Implementation of the Logistic Regression Model and its Applications (JOURNAL OF ADVANCES IN MATHEMATICS, 2020)
The purpose of an analysis using this method is the same as that of any technique in constructing models in statistics, namely to find the best and most reasonable model to describe the relationship between a result variable and a set of variables independent. We are interested in how the costs affect them and if a customer has a travel card.Credit card customers are shown to be 6 times more likely to use it regardless of the cost they make.It is also shown that a customer is more likely to use a travel card when costs increase Through logistic regression, which gives the probability that a result is an exponential function of the independent variables, we will see how through our data we will come to very important conclusions.